Gruppenaufnahme
Mitglieder Bundesvorstand Die Grünen Petra Kelly, Erich Knapp, Christiane Schnappertz, Eva Reichelt, Norbert Mann, Rolf Stolz, Bettina Höltje, Dieter Burgmann, Ursula Alverdes und Hannelore Saibold;